2017
DOI: 10.1117/1.jmi.4.3.033502
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and CT sampling characterization of a third-generation SPECT–CT system for dedicated breast imaging

Abstract: Stand-alone cone beam computed tomography (CT) and single-photon emission computed tomography (SPECT) systems capable of complex acquisition trajectories have previously been developed for breast imaging. Fully three-dimensional (3-D) motions of SPECT systems provide views into the chest wall and throughout the entire volume. The polar tilting capability of the CBCT system has shown improvement in sampling close to the chest wall, while eliminating cone beam artifacts. Here, a single hybrid SPECT-CT system, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Modulation transfer function (MTF) and sampling studies [7] were performed in the past using tilted trajectories in addition to x-ray scatter [25] and dose distribution [9] studies. We have recently also developed a tilt capable, hybrid SPECT-CT system where each modality is independently capable of traversing 3D orbits [28]. However, a comprehensive characterization of HU values for these systems having capability of different 3D trajectories, and comparison with standard metrics has never been performed for titled 3D trajectories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulation transfer function (MTF) and sampling studies [7] were performed in the past using tilted trajectories in addition to x-ray scatter [25] and dose distribution [9] studies. We have recently also developed a tilt capable, hybrid SPECT-CT system where each modality is independently capable of traversing 3D orbits [28]. However, a comprehensive characterization of HU values for these systems having capability of different 3D trajectories, and comparison with standard metrics has never been performed for titled 3D trajectories.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies did not consider the effect of different acquisition orbits on linear attenuation coefficients. For tilted trajectories, as the polar tilt angle of the system changes, the angle of incidence of the x-ray beam changes, thereby changing the path lengths of the x-rays incident on the target volume [28, 30]. This results in differences in the dose distribution [9], and scatter distribution [10], which in turn would affect the reconstructed absolute attenuation coefficients and thereby the HU values.…”
Section: Introductionmentioning
confidence: 99%
“…Dedicated breast CT has been studied over the past few years (19). Additionally, other CT based multimodality based systems (SPECT-CT and PET-CT) have also been developed, however, the use of these systems in the clinic remains limited, given the potential radiation safety issues for screening in younger women (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Lindfors et al developed a cone-beam breast-CT, in which visualization of masses was significantly better compared to mammography, but visualization of MCs was significantly worse [ 14 ]. Shah et al constructed a tilt-capable combination of SPECT and cone beam-CT to gain a better sampling of breast tissue close to the chest wall [ 15 ]. Evaluation of a commercially available cone-beam breast-CT showed that detection of malignant lesions, including DCIS, was superior compared to mammography, but results regarding the detection of MCs are lacking [ 16 ].…”
Section: Introductionmentioning
confidence: 99%